The semicentennial binary system PSR J2032+4127 at periastron: X-ray photometry, optical spectroscopy, and SPH modelling. Issue 2 (20th February 2019) - Coe, M J; Okazaki, A T; Steele, I A; Ng, C-Y; Ho, Wynn C G; Lyne, A G; Stappers, B; Johnson, T J; Ray, Paul S; Kerr, M
Abstract: X-ray photometry and optical spectra are presented covering the periastron passage of the highly eccentric, ∼50 yr binary system PSR J2032+4127 in 2017 November. This system consists of a 143 ms pulsar in orbit around a massive OB star, MT 91-213. The data show dramatic changes during the encounter as the pulsar wind collided with the stellar wind. The X-ray flux rose on the approach to periastron, then underwent a major dip in the few days around periastron, and then gradually declined over the next few weeks. The optical spectroscopy revealed a steady decline in the H α line strength on the approach to periastron (from an equivalent width of −15 to −7 Å) implying a truncation of the OB star's circumstellar disc by the approaching neutron star. Smooth particle hydrodynamic modelling is used here to model the system within the context of the observed behaviour and predict the geometrical configuration of the circumstellar disc with respect to the pulsar's orbit.